Priežasties santykiai tekstemų ir predikatinių dėmenų pakopoje - Našlėnaitė-Eberhardt, Vaida (Kalbotyra, 2001)
The article deals with the phenomenon of causal relations in two largest text units of Modern Lithuanian, i.e. both – in the paragraph and in predicate constructions. It has the aim to analyse structural types and syntactic means of causal constructions. The main semantic features – the category of binary as well as semantic components of the cause are reviewed. The problem of distinguishing causal relations from other relations which are semantically close to the causal relations may be solved by substituting the clauses and sometimes by translating the clauses into Latvian. The general characteristics of the control linkage of causal constructions enable us to analyse different text units simultaneously. And other reason for such analysis is the usage of the same connectors in the paragraph as well as in predicate constructions. Analysis of the causal markers in the paragraph helps us to identify the semantic relations in the texts units. Possible means of connection between predicative constructions with the causal relations in the paragraph are presented in a table, which also shows the distribution of these constructions as well as their connectors in the paragraph.